Electrolyte, lithium metal battery and electric equipment

By using halogenated hydrocarbon-containing electrolyte in lithium-ion batteries, the problem of SEI film prone to rupture is solved, and the coulombic efficiency, cycle performance and safety performance of the battery are improved.

CN119852518APending Publication Date: 2025-04-18CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311352000.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-18
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

During the charging and discharging cycle of existing lithium-ion batteries, the SEI membrane is prone to rupture, resulting in electrolyte consumption, increasing safety risks, and reducing Coulomb efficiency and circulation performance.

Method used

The electrolyte containing halogenated hydrocarbons is used as an additive to improve the mechanical strength and stability of the SEI film, inhibit the rupture of the SEI film during lithium deposition and peeling, and serve as a diluent to improve the fluidity and ionic conductivity of the electrolyte.

Benefits of technology

Effectively inhibit the rupture of SEI membrane, extend the service life of the electrolyte, and improve the Coulomb efficiency, circulation performance and safety performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852518A_ABST
    Figure CN119852518A_ABST
Patent Text Reader

Abstract

The invention relates to an electrolyte, a lithium metal battery and electric equipment, and belongs to the technical field of batteries. The electrolyte comprises a lithium salt, a solvent and an additive, wherein the additive is halogenated hydrocarbon; the halogenated hydrocarbon is a compound containing carbon atoms, hydrogen atoms and fluorine halogen atoms; the halogen atoms include fluorine atoms. The electrolyte provided by the invention contains halogenated hydrocarbon as an additive, so that the cracking of an SEI film in the lithium deposition and stripping process can be inhibited, the short circuit phenomenon of the lithium ion battery can be avoided, and the coulombic efficiency, the cycle performance and the safety performance of the lithium ion battery can be improved at the same time. And the halogenated hydrocarbon is also used as a diluent, so that the problems of poor wettability, high viscosity, low ionic conductivity and the like caused by high salt concentration of the electrolyte can be avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an electrolyte, a lithium metal battery and an electrical device. Background Art

[0002] Lithium-ion batteries have outstanding advantages such as high energy density, low self-discharge rate, long cycle life and stable discharge performance. They are widely used in industrial production and people's daily life.

[0003] During the charging process of lithium-ion batteries, lithium ions are released from the positive electrode active material, transported through the electrolyte, passed through the isolation membrane, and embedded in the negative electrode active layer. The electrolyte reacts at the solid-liquid interface of the anode to form a passivation layer, which is the solid electrolyte interface layer (SEI film), which has the characteristics of a solid electrolyte and an electronic insulator, but is also a good conductor of lithium ions.

[0004] In existing lithium-ion batteries, as the charge and discharge cycle of the lithium-ion battery proceeds, the deposition and stripping of lithium will cause the SEI film to be continuously destroyed and regenerated, and the electrolyte is continuously consumed. The SEI film is easily broken and flows with the electrolyte, which can easily cause the lithium-ion battery to short-circuit, causing safety hazards, and the coulombic efficiency and cycle performance of the lithium-ion battery will also be reduced. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present application provides an electrolyte, a lithium metal battery and an electrical device to inhibit the rupture of the SEI film during lithium deposition and stripping, while improving the coulombic efficiency, cycle performance and safety performance of lithium-ion batteries.

[0006] In a first aspect, the present application provides an electrolyte, which includes a lithium salt, a solvent and an additive; wherein the additive is a halogenated hydrocarbon; the halogenated hydrocarbon is a compound containing carbon atoms, hydrogen atoms and fluorine halogen atoms; and the halogen atoms include fluorine atoms.

[0007] The electrolyte of the present application contains halogenated hydrocarbons. As additives, halogenated hydrocarbons can improve the mechanical strength and stability of SEI, inhibit the rupture of SEI film during lithium deposition and stripping, reduce the side reaction of lithium metal and electrolyte, and help avoid short circuit of lithium ion batteries. It can also improve the coulombic efficiency, cycle performance and safety performance of lithium ion batteries. The inventors analyzed that the reason may be that the halogenated hydrocarbons themselves will defluorinate during the cycle of lithium ion batteries to generate carbon chains with a large number of unsaturated bonds. Polymerization reaction can occur between these unsaturated carbon chains to form polymer chains with higher toughness. The polymer chains can be compounded with components in the SEI film to form a dense inorganic-organic composite SEI film, thereby improving the mechanical strength and stability of SEI and inhibiting the rupture of SEI film during lithium deposition and stripping.

[0008] In addition, halogenated hydrocarbons can also be used as diluents, which helps to avoid problems such as poor wettability, high viscosity and low ion conductivity caused by high salt concentration of the electrolyte, thereby helping to improve the cycle performance, rate performance and safety performance of lithium-ion batteries.

[0009] In some embodiments, the halogen atom is a fluorine atom, that is, the halogenated hydrocarbon contains only carbon atoms, hydrogen atoms and fluorine atoms, which can slow down the consumption rate of the electrolyte and help further improve the cycle performance of the lithium-ion battery.

[0010] In some embodiments, the molar ratio of lithium salt, solvent and additive is 1:(0.8-3):(0.02-3). The lithium salt, solvent and additive in the above ratio can fully exert the energy density of the lithium-ion battery and make the halogenated hydrocarbon as an additive fully exert its effect, so that the lithium-ion battery has better cycle performance, higher coulombic efficiency and is not prone to short circuit.

[0011] In some embodiments, the molar ratio of lithium salt, solvent and additive is 1:(1.2-2.4):(0.05-2). The lithium salt, solvent and additive in the above ratio can fully exert the energy density of the lithium-ion battery and make the halogenated hydrocarbon as an additive fully exert its effect, so as to further improve the cycle performance, coulombic efficiency and safety performance of the lithium-ion battery.

[0012] In some embodiments, the halogenated hydrocarbon has ≤20 carbon atoms.

[0013] In some embodiments, the halogenated hydrocarbon has a branched structure, and the main chain and the branched structure of the halogenated hydrocarbon have fluorine atoms. This is conducive to further improving the compactness of the inorganic-organic composite SEI film formed subsequently, and thus is conducive to further improving the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery at the same time; the inventors analyzed that the reason may be: the main chain and the branched structure of the halogenated hydrocarbon have fluorine atoms, which is conducive to the formation of a carbon chain with a large number of unsaturated bonds after the halogenated hydrocarbon is defluorinated, and the unsaturated carbon chains can undergo polymerization to form a polymer chain with high toughness. The branched chain of the polymerized carbon chain forms a double bond after defluorination, which can make the polymerized carbon chains cross-linked to each other through the double bonds on the branched chain to form a cross-linked network, making it easier to form a dense inorganic-organic composite SEI film.

[0014] In some embodiments, the halogenated hydrocarbon has a ring structure. The presence of the ring structure in the halogenated hydrocarbon can give the formed inorganic-organic composite SEI film a certain toughness, can improve the mechanical strength of the SEI film, and is conducive to further inhibiting the rupture of the SEI film during lithium deposition and stripping, thereby further improving the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery at the same time.

[0015] In some embodiments, the ratio of the number of fluorine atoms to the number of hydrogen atoms in the halogenated hydrocarbon is 2 to 9. The ratio of the number of fluorine atoms to the number of hydrogen atoms in the halogenated hydrocarbon within the above range is beneficial for taking into account the redox stability of the lithium ion battery and for forming a more stable and dense SEI film, so as to simultaneously improve the coulombic efficiency, cycle performance and safety performance of the lithium ion battery.

[0016] In some embodiments, at least two adjacent carbon atoms in the halogenated hydrocarbon are connected to fluorine atoms. A dense inorganic-organic composite SEI film can be formed, which is beneficial to inhibit the rupture of the SEI film during lithium deposition and stripping, thereby simultaneously improving the coulombic efficiency, cycle performance and safety performance of lithium-ion batteries; the inventors analyzed that the reason may be: at least two adjacent carbon atoms in the halogenated hydrocarbon are connected to fluorine atoms, which can make the halogenated hydrocarbon more prone to defluorination reaction to form unsaturated carbon chains, and polymerization reactions can occur between the unsaturated carbon chains to form polymer chains with higher toughness, which can be compounded with the components in the SEI film to form a dense inorganic-organic composite SEI film, thereby improving the mechanical strength and stability of the SEI, and inhibiting the rupture of the SEI film during lithium deposition and stripping.

[0017] In some embodiments, the halogenated hydrocarbon has unsaturated bonds. The presence of unsaturated bonds in the halogenated hydrocarbon is conducive to further improving the compactness of the subsequently formed inorganic-organic composite SEI film, and thus is conducive to further improving the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery at the same time; the inventors analyzed that the reason may be: the halogenated hydrocarbon itself will defluorinate during the cycle of the lithium-ion battery to generate a carbon chain with a large number of unsaturated bonds, and the unsaturated carbon chains can undergo polymerization to form polymer chains with higher toughness; and because the halogenated hydrocarbon itself has unsaturated bonds, the polymerized carbon chains can be cross-linked to form a cross-linked network through the unsaturated bonds of the halogenated hydrocarbon itself, which makes it easier to form a dense inorganic-organic composite SEI film.

[0018] In some embodiments, the number of carbon atoms of the halogenated hydrocarbon is 5 to 7. The number of carbon atoms of the halogenated hydrocarbon within the above range is conducive to further improving the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery at the same time; the inventors analyzed that the reason may be: the number of carbon atoms of the halogenated hydrocarbon is 5 to 7, which can make the molecular volume of the halogenated hydrocarbon more appropriate, which is conducive to making the polymer chain formed by the polymerization of the unsaturated carbon chain generated after the defluorination of the halogenated hydrocarbon and the inorganic components of the SEI film more closely combined, which is conducive to improving the compactness of the formed inorganic-organic composite SEI film, and thus can inhibit the rupture of the SEI film during lithium deposition and stripping.

[0019] In some embodiments, the additive comprises at least one of the halogenated hydrocarbons represented by Formula I, the halogenated hydrocarbons represented by Formula II, and the halogenated hydrocarbons represented by Formula III; Formula I is: C m1 H 2(m1)+2-n1F n1 , 8≥m1≥4, n1<2×m1+2; Formula II is: C m2 H 2(m2)- n2 F n2 , 8≥m2≥4, n2<2×m2; Formula III is: C m3 H 2(m3)-2-n3 F n3 , 8≥m3≥4, n3<2×m3-2. The halogenated hydrocarbon is selected from the chemical formula shown in the above formula I, formula II or formula III, which can form a dense SEI film during the cycle of the lithium ion battery, which is beneficial to inhibit the rupture of the SEI film during lithium deposition and stripping, and can simultaneously improve the coulombic efficiency, cycle performance and safety performance of the lithium ion battery.

[0020] In some embodiments, the additive is a halogenated hydrocarbon shown in Formula III. The halogenated hydrocarbon shown in Formula III has a degree of unsaturation of 2, which is conducive to forming a more compact and structurally stable inorganic-organic composite SEI film, and is conducive to inhibiting the rupture of the SEI film during lithium deposition and stripping, so as to further improve the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery at the same time.

[0021] In some embodiments, the additive is selected from at least one of the following compounds:

[0022]

[0023]

[0024]

[0025] The additives are selected from the above compounds, which can form a dense and structurally stable SEI film during the cycle of the lithium-ion battery, which is beneficial to inhibit the rupture of the SEI film during lithium deposition and stripping, and can simultaneously improve the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery.

[0026] In some embodiments, the lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium difluorooxalatoborate. The lithium source is selected from the above substances to form an inorganic fluorine-rich SEI film component, which is beneficial to further improve the cycle performance of the lithium-ion battery.

[0027] In some embodiments, the solvent is selected from ether solvents.

[0028] In some embodiments, the solvent is selected from at least one of methyl n-butyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, 1,2-dimethoxypropane, and 1,3-dimethoxypropane.

[0029] In some embodiments, the electrolyte further includes a diluent, and the diluent is selected from at least one of fluoroether, benzene and anisole. The electrolyte contains a diluent, and the diluent is selected from the above substances, which can improve the problems of high electrolyte viscosity, poor wettability with the diaphragm and low ion conductivity caused by high salt concentration of the electrolyte, and is conducive to improving the cycle performance, rate performance and safety performance of the lithium-ion battery.

[0030] In some embodiments, the molar ratio of the diluent to the lithium salt is ≤ 5. The molar ratio of the diluent to the lithium salt can improve the cycle performance of the lithium ion battery under the above ratio.

[0031] In some embodiments, the additive accounts for 15% to 25% of the total molar amount of the lithium salt, the solvent and the diluent. When the electrolyte contains a diluent, the additive within the above dosage range can form a dense SEI film during the cycle of the lithium ion battery, which is beneficial to inhibit the rupture of the SEI film during lithium deposition and stripping, and can improve the coulombic efficiency, cycle performance and safety performance of the lithium ion battery.

[0032] In some embodiments, the fluoroether is selected from at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl, 1-(1,1,2,2-tetrafluoroethoxy)propane, 1,1,2,2-tetrafluoroethyl ethyl ether, and bis-bis(2,2,2-trifluoroethyl) ether.

[0033] In a second aspect, the present application provides a lithium metal battery, the lithium metal battery comprising the electrolyte provided in any one of the first aspects. The lithium metal battery provided in the present application can inhibit the rupture of the SEI film during lithium deposition and stripping, and can simultaneously improve the coulombic efficiency, cycle performance, and safety performance of the lithium metal battery.

[0034] In a third aspect, the present application provides an electrical device, which includes the lithium metal battery provided in the second aspect.

[0035] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 A schematic diagram of the structure of a vehicle provided for some embodiments of the present application.

[0038] Figure 2 Schematic diagram of the exploded structure of a battery provided for some embodiments of the present application.

[0039] Figure 3 A schematic diagram of the structure of a battery cell provided in some embodiments of the present application.

[0040] Figure 4 An exploded view of a battery cell provided for some embodiments of the present application.

[0041] Figure 5 The optical microscope images of the surface of the negative electrode sheet in contact with the separator and the surface of the separator in contact with the negative electrode sheet after the battery cell of Example 2 was cycled 100 times are shown.

[0042] Figure 6 An enlarged optical microscope image of the surface of the negative electrode sheet in contact with the separator after the battery cell of Example 2 has been cycled 100 times is shown.

[0043] Figure 7 The optical microscope images of the surface of the negative electrode plate in contact with the separator and the surface of the separator in contact with the negative electrode plate after the battery cell of Example 11 was cycled 100 times are shown.

[0044] Figure 8 An enlarged optical microscope image of the surface of the negative electrode sheet in contact with the separator after the battery cell of Example 11 has been cycled 100 times is shown.

[0045] Fig. 9 The optical microscope images of the surface of the negative electrode plate in contact with the separator and the surface of the separator in contact with the negative electrode plate after the battery cell of Comparative Example 1 was cycled 100 times are shown.

[0046] Fig.10 An enlarged optical microscope image of the surface of the negative electrode sheet in contact with the separator after the battery cell of Comparative Example 1 has been cycled 100 times is shown.

[0047] Fig.11 The optical microscope images of the surface of the negative electrode plate in contact with the separator and the surface of the separator in contact with the negative electrode plate after the battery cell of Comparative Example 3 was cycled 100 times are shown.

[0048] Fig.12 An enlarged optical microscope image of the surface of the negative electrode sheet in contact with the separator after the battery cell of Comparative Example 3 has been cycled 100 times is shown.

[0049] Icons: 1000-vehicle; 100-battery; 10-casing; 11-accommodating space; 12-first part; 13-second part; 20-battery cell; 21-casing; 211-opening; 22-end cover assembly; 221-end cover; 222-electrode terminal; 23-electrode assembly; 24-current collecting member; 25-insulating protection member; 200-controller; 300-motor. DETAILED DESCRIPTION

[0050] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0051] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0052] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0053] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0054] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0055] In the description of the embodiments of the present application, the orientation or position relationship indicated by the technical terms "thickness", "bottom", "inside" and "outside" are based on the orientation or position relationship shown in the accompanying drawings, which is only for the convenience of describing the embodiments of the present application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.

[0056] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installation", "connection", "fixation" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0057] At present, from the perspective of market development, the application of power batteries is becoming more and more extensive. Power batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of the application field of power batteries, the market demand is also constantly expanding.

[0058] The power battery can be a lithium-ion battery. During the charging process of the lithium-ion battery, lithium ions are released from the positive electrode active material, transmitted through the electrolyte, passed through the isolation membrane, and embedded in the negative electrode active layer. However, as the charge and discharge cycle of the lithium-ion battery proceeds, the existing lithium-ion batteries generally have the problem of rapid cycle life exhaustion, especially for lithium metal batteries that use metallic lithium or lithium alloys as negative electrode active materials, the exhaustion rate of their cycle life is more obvious. Metallic lithium or lithium alloys have high reactivity and will spontaneously react with the electrolyte, and quickly consume the electrolyte, thereby causing the rapid exhaustion of the lithium metal battery cycle life. Therefore, in order to improve the cycle life of lithium-ion batteries, especially to improve the cycle life of lithium metal batteries that use metallic lithium or lithium alloys as negative electrode active materials, the design and optimization of the electrolyte composition is crucial.

[0059] Different from the ester electrolytes used in traditional lithium-ion batteries for a long time, many ether electrolytes have been widely used in lithium-ion batteries in recent years, especially lithium metal batteries using metallic lithium or lithium alloys as negative electrode active materials. However, ether electrolytes are not resistant to oxidation and are incompatible with high-voltage positive electrode materials such as lithium cobalt nickel manganese oxide (LiCoNiMnO4, NCM811), making it difficult to operate stably at high voltages. Therefore, high-concentration lithium salt electrolytes or local high-concentration lithium salt electrolytes are currently used to adjust the solvation structure of contact ion pairs (CIPs) and ion aggregates (AGGs), thereby improving their high-voltage tolerance. The use of high-concentration lithium salt electrolytes or local high-concentration lithium salt electrolytes also has problems such as high electrolyte viscosity, poor wettability, and low ionic conductivity. Therefore, diluents are currently used to improve the poor wettability, high viscosity, and low ionic conductivity caused by reducing the high salt concentration of the electrolyte.

[0060] However, the inventors have found that in the actual charge and discharge cycle of lithium-ion batteries, as the charge and discharge cycle of lithium-ion batteries proceeds, the deposition and stripping of lithium will cause the SEI film to be continuously destroyed and regenerated, and the electrolyte is continuously consumed. The SEI film is prone to breakage and flow with the electrolyte, which can easily lead to a short circuit in the lithium-ion battery, causing a safety hazard, and the coulombic efficiency and cycle performance of the lithium-ion battery will also be reduced.

[0061] The inventors analyzed that since the main components of the SEI film are inorganic particles, the SEI film is relatively loose, so the SEI film with poor stability is easy to break and flow with the electrolyte, which reduces the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery. In particular, for lithium metal batteries using metallic lithium or lithium alloys as negative electrode active materials, metallic lithium or lithium alloys have high reactivity and will spontaneously react with the electrolyte to generate SEI films with low mechanical strength and poor chemical stability, causing the SEI film to form a dendritic growth morphology. The SEI film is more likely to break and flow with the electrolyte, bringing safety risks, and the rapid consumption of lithium sources will also cause the cycle life of lithium-ion batteries to be exhausted.

[0062] Based on the above considerations, in order to inhibit the rupture of the SEI film during lithium deposition and stripping, and at the same time improve the coulombic efficiency, cycle performance and safety performance of lithium-ion batteries, the present application designs an electrolyte, which includes a lithium salt, a solvent and an additive; wherein the additive is a halogenated hydrocarbon; the halogenated hydrocarbon is a compound containing carbon atoms, hydrogen atoms and fluorine halogen atoms; the halogen atoms include fluorine atoms.

[0063] The electrolyte of the present application contains halogenated hydrocarbons. As additives, halogenated hydrocarbons can improve the mechanical strength and stability of SEI, inhibit the rupture of SEI film during lithium deposition and stripping, reduce the side reaction between lithium metal and electrolyte, and help avoid short circuit in lithium ion batteries. It can also improve the coulombic efficiency, cycle performance and safety performance of lithium ion batteries. The inventors analyzed that the reason may be that the halogenated hydrocarbons themselves will defluorinate during the cycle of lithium ion batteries to generate carbon chains with a large number of unsaturated bonds. Polymerization reactions can occur between these carbon chains to form polymer chains with high toughness. The polymer chains can be compounded with components in the SEI film to form a dense inorganic-organic composite SEI film, thereby improving the mechanical strength and stability of SEI and inhibiting the rupture of SEI film during lithium deposition and stripping.

[0064] In addition, halogenated hydrocarbons can also be used as diluents, which helps to avoid problems such as poor wettability, high viscosity and low ion conductivity caused by high salt concentration of the electrolyte, thereby helping to improve the cycle performance, rate performance and safety performance of lithium-ion batteries.

[0065] The electrolyte can be assembled with the positive electrode sheet, the negative electrode sheet and the separator into a battery, and the battery can be a battery cell, a module, a battery pack, etc. The battery can be used in, but not limited to, electrical equipment such as vehicles, ships or aircraft. The battery disclosed in this application can be used to form a power supply system for the electrical equipment, which is conducive to improving the cycle performance and service life of the battery at higher temperatures.

[0066] The embodiment of the present application provides an electric device that uses a battery as a power source. The electric device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy, an electric tool, and the like. The vehicle can be a fuel vehicle, a gas vehicle, or a new energy vehicle. The new energy vehicle can be a pure electric vehicle, a hybrid vehicle, or an extended-range vehicle, and the like; the spacecraft includes an airplane, a rocket, a space shuttle, and a spacecraft, and the like; the electric toy includes a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, and the like; the electric tool includes a metal cutting electric tool, a grinding electric tool, an assembly electric tool, and an electric tool for railways, such as an electric drill, an electric grinder, an electric wrench, an electric screwdriver, an electric hammer, an impact drill, a concrete vibrator, and an electric planer, and the like. The embodiment of the present application does not impose any special restrictions on the above-mentioned electric devices.

[0067] For the convenience of description, the following embodiments are described by taking the electric device as a vehicle as an example.

[0068] Please refer to Figure 1 , Figure 1The schematic diagram of the structure of the vehicle 1000 provided in some embodiments of the present application. The vehicle 1000 is provided with a battery 100 inside, and the battery 100 can be provided at the bottom, head or tail of the vehicle 1000. The battery 100 can be used to power the vehicle 1000, for example, the battery 100 can be used as an operating power source of the vehicle 1000.

[0069] The vehicle 1000 may further include a controller 200 and a motor 300 , wherein the controller 200 is used to control the battery 100 to supply power to the motor 300 , for example, to meet the power requirements of starting, navigating, and driving the vehicle 1000 .

[0070] In some embodiments of the present application, the battery 100 can not only serve as an operating power source for the vehicle 1000, but also serve as a driving power source for the vehicle 1000, replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000.

[0071] Figure 2 This is a schematic diagram of the exploded structure of the battery 100 provided in some embodiments of the present application. Figure 2 The battery 100 includes a housing 10 and a battery cell 20 , and the battery cell 20 is accommodated in the housing 10 .

[0072] The box body 10 is used to provide a storage space 11 for the battery cell 20. In some embodiments, the box body 10 may include a first portion 12 and a second portion 13, and the first portion 12 and the second portion 13 cover each other to define the storage space 11 for accommodating the battery cell 20. Of course, the connection between the first portion 12 and the second portion 13 can be sealed by a sealing member (not shown in the figure), and the sealing member can be a sealing ring, a sealant, etc.

[0073] The first part 12 and the second part 13 can be in various shapes, such as a cuboid, a cylinder, etc. The first part 12 can be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20, and the second part 13 can also be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20. The opening side of the second part 13 covers the opening side of the first part 12, thereby forming a box body 10 with a receiving space 11. Of course, if Figure 2 As shown, the first part 12 may be a hollow structure with one side open, and the second part 13 may be a plate-like structure. The second part 13 covers the open side of the first part 12 to form a box body 10 with an accommodating space 11.

[0074] In the battery 100, there can be one or more battery cells 20. If there are more than one battery cell 20, the battery cells 20 can be connected in series, in parallel or in a mixed connection. A mixed connection means that the battery cells 20 are connected in series and in parallel. The battery cells 20 can be directly connected in series, in parallel or in a mixed connection, and then the whole formed by the battery cells 20 can be accommodated in the box 10; of course, the battery cells 20 can be connected in series, in parallel or in a mixed connection to form a battery module, and then the battery modules can be connected in series, in parallel or in a mixed connection to form a whole, and then accommodated in the box 10. The battery cell 20 can be cylindrical, flat, rectangular or in other shapes. Figure 2 The example shows that the battery cell 20 is in a square shape.

[0075] In some embodiments, the battery 100 may further include a busbar component (not shown), and the multiple battery cells 20 may be electrically connected via the busbar component to achieve series connection, parallel connection, or mixed connection of the multiple battery cells 20 .

[0076] Figure 3 This is a schematic diagram of the structure of a battery cell 20 provided in some embodiments of the present application. Figure 4 This is an exploded view of a battery cell 20 provided in some embodiments of the present application. Figure 3 and Figure 4 The battery cell 20 may include a housing 21 , an end cap assembly 22 and an electrode assembly 23 . The housing 21 has an opening 211 , the electrode assembly 23 is accommodated in the housing 21 , and the end cap assembly 22 is used to cover the opening 211 .

[0077] The shape of the housing 21 can be determined according to the specific shape of the electrode assembly 23. For example, if the electrode assembly 23 is a rectangular parallelepiped structure, the housing 21 can be a rectangular parallelepiped structure. Figure 3 and Figure 4 The case where the housing 21 and the electrode assembly 23 are square is exemplarily shown.

[0078] The shell 21 may also be made of a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, etc., and the embodiment of the present application does not impose any special restrictions on this.

[0079] The end cap assembly 22 includes an end cap 221 and an electrode terminal 222. The end cap assembly 22 is used to seal the opening 211 of the housing 21 to form a closed installation space (not shown), and the installation space is used to accommodate the electrode assembly 23. The installation space is also used to accommodate an electrolyte, such as an electrolyte. The end cap assembly 22 is a component for outputting the electrical energy of the electrode assembly 23. The electrode terminal 222 in the end cap assembly 22 is used to be electrically connected to the electrode assembly 23, that is, the electrode terminal 222 is electrically connected to the tab of the electrode assembly 23. For example, the electrode terminal 222 is connected to the tab through the current collecting member 24 to achieve electrical connection between the electrode terminal 222 and the tab.

[0080] It should be noted that the opening 211 of the shell 21 can be one or two. If the opening 211 of the shell 21 is one, the end cap assembly 22 can also be one, and two electrode terminals 222 can be provided in the end cap assembly 22, and the two electrode terminals 222 are respectively used to electrically connect to the positive pole ear and the negative pole ear of the electrode assembly 23. If the opening 211 of the shell 21 is two, for example, the two openings 211 are provided on opposite sides of the shell 21, the end cap assembly 22 can also be two, and the two end cap assemblies 22 are respectively covered at the two openings 211 of the shell 21. In this case, the electrode terminal 222 in one end cap assembly 22 can be a positive electrode terminal, which is used to electrically connect to the positive pole ear of the electrode assembly 23; the electrode terminal 222 in the other end cap assembly 22 can be a negative electrode terminal, which is used to electrically connect to the negative pole piece of the electrode assembly 23.

[0081] In some embodiments, Figure 4 As shown, the battery cell 20 may further include an insulating protective member 25 fixed to the periphery of the electrode assembly 23, and the insulating protective member 25 is used to insulate and isolate the electrode assembly 23 from the housing 21. Exemplarily, the insulating protective member 25 is a tape bonded to the periphery of the electrode assembly 23. In some embodiments, there are multiple electrode assemblies 23, and the insulating protective member 25 is arranged around the periphery of the multiple electrode assemblies 23, and the multiple electrode assemblies 23 are formed into an integral structure to maintain the stability of the electrode assembly 23 structure. Among them, the electrode assembly 23 can be a wound electrode assembly or a laminated electrode assembly, and the embodiments of the present application are not limited thereto.

[0082] The electrode assembly 23 includes a positive electrode sheet, a negative electrode sheet and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet. The electrolyte is located in the installation space and filled in the gap of the electrode assembly 23.

[0083] The present application has no particular restrictions on the positive electrode sheet, the negative electrode sheet and the separator.

[0084] The isolation membrane can be a PP (polypropylene) porous membrane, a PE (polyethylene) porous membrane, a polyimide porous membrane, and a porous membrane formed by a composite of multiple polymers.

[0085] The positive electrode sheet includes a positive electrode current collector and a positive electrode active layer covering at least one surface of the positive electrode current collector in the thickness direction; the material of the positive electrode current collector may include aluminum foil, foamed aluminum, aluminum composite current collector (a current collector with a polymer support layer in the middle and aluminum metal layers on both surfaces of the support layer), nickel foil, foamed nickel, etc.; the positive electrode active material in the positive electrode active layer includes one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and olivine structure lithium-containing phosphate, for example, nickel cobalt manganese oxide Lithium, lithium nickel cobalt aluminum oxide, lithium cobalt oxide, lithium iron phosphate, lithium manganate, etc.; the binder in the positive electrode active layer is selected from at least one of vinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyacrylate, carboxymethyl cellulose sodium salt, styrene-butadiene rubber, polyurethane, ethylene-vinyl acetate copolymer and ethylene-acrylic acid copolymer; the dispersant in the positive electrode active layer is selected from polyvinyl pyrrolidone, etc.; the conductive particles in the positive electrode active layer are selected from at least one of conductive carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, graphene, activated carbon, graphite sheets, graphite particles and mesophase carbon microspheres.

[0086] The negative electrode plate includes a negative electrode current collector and a negative electrode active layer covering at least one surface of the negative electrode current collector in the thickness direction; the material of the negative electrode current collector may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a polymer substrate covered with a conductive metal, etc., wherein the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate and poly(p-phenylene terephthalamide); the negative electrode active material in the negative electrode active layer includes lithium, an alloy formed by lithium and other metal elements or non-metal elements, wherein the metal elements include tin (Sn), zinc (Zn), aluminum (Al), magnesium (Mg), silver (Ag), gold (Au), gallium (Ga), indium (In), foil (Pt), etc., and the non-metal elements include boron (B), carbon (C), silicon (Si), etc.

[0087] In the present application, the electrolyte includes a lithium salt, a solvent and an additive; wherein the additive is a halogenated hydrocarbon; the halogenated hydrocarbon is a compound containing carbon atoms, hydrogen atoms and halogen atoms; the halogen atoms include fluorine atoms.

[0088] Herein, “the electrolyte includes lithium salt, solvent and additive” means that the electrolyte may contain only lithium salt, solvent and additive, or the electrolyte may contain other ingredients in addition to lithium salt, solvent and additive, such as conventional diluent (at least one of fluoroether, benzene and anisole), etc.

[0089] The fact that the additive is a halogenated hydrocarbon does not necessarily mean that the additive has only one halogenated hydrocarbon with one chemical formula, but may also mean that the additive has a plurality of halogenated hydrocarbons with different chemical formulas.

[0090] In the technical solution provided in the embodiment of the present application, the electrolyte contains halogenated hydrocarbons. As additives, the halogenated hydrocarbons can improve the mechanical strength and stability of SEI, inhibit the rupture of SEI film during lithium deposition and stripping, reduce the side reaction between lithium metal and electrolyte, and help avoid short circuit in lithium-ion batteries. It can also improve the coulombic efficiency, cycle performance and safety performance of lithium-ion batteries. The inventors analyzed that the reason may be that the halogenated hydrocarbons themselves will defluorinate during the cycle of lithium-ion batteries to generate carbon chains with a large number of unsaturated bonds. Polymerization reactions can occur between these carbon chains to form polymer chains with higher toughness. The polymer chains can be compounded with the components in the SEI film to form a dense inorganic-organic composite SEI film, thereby improving the mechanical strength and stability of SEI and inhibiting the rupture of SEI film during lithium deposition and stripping.

[0091] In addition, halogenated hydrocarbons can also be used as diluents, which helps to avoid problems such as poor wettability, high viscosity and low ion conductivity caused by high salt concentration of the electrolyte, thereby helping to improve the cycle performance, rate performance and safety performance of lithium-ion batteries.

[0092] Compared with fluoroethers, benzene, anisole and traditional chlorinated hydrocarbon additives used as diluents, halogenated hydrocarbons in the electrolyte can inhibit the rupture of the SEI film during lithium deposition and stripping, while improving the coulombic efficiency, cycle performance and safety performance of lithium-ion batteries.

[0093] In some embodiments, the halogen atom is a fluorine atom, that is, the halogenated hydrocarbon contains carbon atoms, hydrogen atoms and fluorine atoms, which can slow down the consumption rate of the electrolyte and help further improve the cycle performance of the lithium-ion battery.

[0094] In some embodiments, in the electrolyte, the molar ratio of lithium salt, solvent and additive is 1:(0.8-3):(0.02-3). The lithium salt, solvent and additive in the above ratio can fully exert the energy density of the lithium-ion battery and make the halogenated hydrocarbon as an additive fully exert its effect, so that the lithium-ion battery has better cycle performance, higher coulombic efficiency and is not prone to short circuit.

[0095] As an example, the molar ratio of lithium salt to solvent can be 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:1.9, 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9 and 1:3, or any range between two values; the molar ratio of lithium salt to additive can be 1:0.02, 1:0.03, 1:0.05, 1:0.07, 1:0.1, 1:0.15, 1:0.2, 1:0. 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9, and 1:3, or any range between any two of the values ​​​​among them.

[0096] Optionally, in the electrolyte, the molar ratio of lithium salt, solvent and additive is 1:(1.2-2.4):(0.05-2); under the above ratio, the lithium salt, solvent and additive can fully exert the energy density of the lithium-ion battery and make the halogenated hydrocarbon as an additive fully exert its effect, so as to further improve the cycle performance, coulombic efficiency and safety performance of the lithium-ion battery.

[0097] In some embodiments, the halogenated hydrocarbon has ≤20 carbon atoms.

[0098] In some embodiments, the number of carbon atoms of the halogenated hydrocarbon is 5 to 7; the number of carbon atoms of the halogenated hydrocarbon within the above range is beneficial to further improve the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery at the same time; the inventors analyzed that the reason may be: the number of carbon atoms of the halogenated hydrocarbon is 5 to 7, which can make the molecular volume of the halogenated hydrocarbon more appropriate, which is beneficial to make the polymer chain formed by the polymerization of the unsaturated carbon chain generated after the defluorination of the halogenated hydrocarbon and the inorganic components of the SEI film more closely combined, which is beneficial to improve the compactness of the formed inorganic-organic composite SEI film, and thus can inhibit the rupture of the SEI film during lithium deposition and stripping.

[0099] As an example, the number of carbon atoms in the halogenated hydrocarbon may be 5, 6 or 7.

[0100] In some embodiments, the halogenated hydrocarbon has a branched structure, and the main chain and the branched structure of the halogenated hydrocarbon have fluorine atoms.

[0101] The present application does not limit the number of branched structures in the halogenated hydrocarbon. As an example, the number of branched structures in the halogenated hydrocarbon can be 1, 2, 3 or 4.

[0102] The halogenated hydrocarbons have a branched structure, and both the main chain and the side chain structure of the halogenated hydrocarbons have fluorine atoms, which is beneficial to further improve the compactness of the subsequently formed inorganic-organic composite SEI film, and thus is beneficial to further improve the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery at the same time; the inventors analyzed that the reason may be: the halogenated hydrocarbons have fluorine atoms on both the main chain and the side chain structure, which is beneficial to the formation of carbon chains with a large number of unsaturated bonds after defluorination of the halogenated hydrocarbons. The unsaturated carbon chains can undergo polymerization reactions to form polymer chains with higher toughness. The side chains of the polymerized carbon chains form double bonds after defluorination, which can make the polymerized carbon chains cross-linked with each other through the double bonds on the side chains to form a cross-linked network, making it easier to form a dense inorganic-organic composite SEI film.

[0103] In some embodiments, the halogenated hydrocarbon has a ring structure.

[0104] The ring structure refers to a ring formed by three or more atoms through chemical bonds.

[0105] The present application does not limit the number of cyclic structures in the halogenated hydrocarbon and the number of atoms in the ring skeleton in the cyclic structure. As an example, the number of cyclic structures in the halogenated hydrocarbon can be 1, 2, or 3, and the cyclic structure can be a three-membered ring, a four-membered ring, a five-membered ring, or a six-membered ring.

[0106] The presence of the ring structure in the halogenated hydrocarbons can give the formed inorganic-organic composite SEI film a certain toughness, which can improve the mechanical strength of the SEI film, and is beneficial to further inhibit the rupture of the SEI film during lithium deposition and stripping, thereby further improving the coulombic efficiency, cycle performance and safety performance of lithium-ion batteries.

[0107] In some embodiments, the ratio of the number of fluorine atoms to the number of hydrogen atoms in the halogenated hydrocarbon is 2 to 9. The ratio of the number of fluorine atoms to the number of hydrogen atoms in the halogenated hydrocarbon within the above range is beneficial for taking into account the redox stability of the lithium ion battery and for forming a more stable and dense SEI film, so as to simultaneously improve the coulombic efficiency, cycle performance and safety performance of the lithium ion battery.

[0108] As an example, the ratio of the number of fluorine atoms to the number of hydrogen atoms in the halogenated hydrocarbon can be 2, 2.3, 3, 4, 5, 6, 7, 8 or 9, etc.

[0109] In some embodiments, in the halogenated hydrocarbon, at least two adjacent carbon atoms are connected with fluorine atoms.

[0110] Herein, “at least two adjacent carbon atoms in the halogenated hydrocarbon are connected to fluorine atoms” means: the halogenated hydrocarbon may have only two adjacent carbon atoms connected to fluorine atoms at the same time; or the halogenated hydrocarbon may have multiple groups of adjacent carbon atoms, and the multiple groups of adjacent carbon atoms are all connected to carbon atoms at the same time.

[0111] At least two adjacent carbon atoms in the halogenated hydrocarbon are connected with fluorine atoms, which can form a dense inorganic-organic composite SEI film, which is beneficial to inhibit the rupture of the SEI film during lithium deposition and stripping, thereby simultaneously improving the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery; the inventor analyzed that the reason may be: at least two adjacent carbon atoms in the halogenated hydrocarbon are connected with fluorine atoms, which can make the halogenated hydrocarbon more susceptible to defluorination reaction to form unsaturated carbon chains, and polymerization reaction can occur between the unsaturated carbon chains to form polymer chains with higher toughness. The polymer chains can be compounded with the components in the SEI film to form a dense inorganic-organic composite SEI film, thereby improving the mechanical strength and stability of the SEI and inhibiting the rupture of the SEI film during lithium deposition and stripping.

[0112] In some embodiments, the halogenated hydrocarbon has unsaturated bonds.

[0113] The unsaturated bond may be a carbon-carbon double bond, a carbon-carbon triple bond or a cyclic structure.

[0114] The presence of unsaturated bonds in halogenated hydrocarbons is conducive to further improving the compactness of the subsequently formed inorganic-organic composite SEI film, which in turn is conducive to further improving the coulombic efficiency, cycle performance and safety performance of lithium-ion batteries at the same time. The inventors analyzed that the reason may be that the halogenated hydrocarbons themselves will defluorinate during the cycle of lithium-ion batteries to generate carbon chains with a large number of unsaturated bonds, and these unsaturated carbon chains can undergo polymerization reactions to form polymer chains with higher toughness. Moreover, since the halogenated hydrocarbons themselves have unsaturated bonds, the polymerized carbon chains can be cross-linked with each other through the unsaturated bonds of the halogenated hydrocarbons themselves to form a cross-linked network, making it easier to form a dense inorganic-organic composite SEI film.

[0115] In some embodiments, the additive comprises at least one of the halogenated hydrocarbons represented by Formula I, the halogenated hydrocarbons represented by Formula II, and the halogenated hydrocarbons represented by Formula III; wherein Formula I is: C m1 H 2(m1)+2-n1 F n1 , 8≥m1≥4, 18>n1≥1, n1<2×m1+2; Formula II is: C m2 H 2(m2)-n2 F n2 , 8≥m2≥4, 16>n2≥1, n2<2×m2; Formula III is: Cm3 H 2(m3)-2-n3 F n3 , 8≥m3≥4, 14>n3≥1, n3<2×m3-2.

[0116] Among them, C m1 H 2(m1)+2-n1 F n1 It means that: in the compound, the number of C atoms is m1, the number of H atoms is 2×m1+2-n1, and the number of F atoms is n1; m1 and n1 are both natural numbers; and the degree of unsaturation of formula I is 0.

[0117] C m2 H 2(m2)-n2 F n2 It means: in the compound, the number of C atoms is m2, the number of H atoms is 2×m2-n2, and the number of F atoms is n2; m2 and n2 are both natural numbers; the unsaturation degree of formula II is 1.

[0118] C m3 H 2(m3)-2-n3 F n3 It means: in the compound, the number of C atoms is m3, the number of H atoms is 2×m3-2-n3, and the number of F atoms is n3; m3 and n3 are both natural numbers; the degree of unsaturation of formula III is 2.

[0119] The halogenated hydrocarbon is selected from the chemical formula shown in the above formula I, formula II or formula III, which can form a dense SEI film during the cycle of the lithium ion battery, which is beneficial to inhibit the rupture of the SEI film during lithium deposition and stripping, and can simultaneously improve the coulombic efficiency, cycle performance and safety performance of the lithium ion battery.

[0120] As an example, in Formula I, m1 can be 4, 5, 6, 7 or 8, "n1<2×m1+2" and n1 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 or 17, etc.; in Formula II, m2 can be 4, 5, 6, 7 or 8, "n2<2×m2" and n2 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15, etc.; in Formula III, m3 can be 4, 5, 6, 7 or 8, "n3<2×m3-2" and n3 can be 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12 or 13, etc.

[0121] Furthermore, in Formula I, 16>n1≥1; in Formula II, 14>n2≥1; in Formula III, 12>n3≥1. This is beneficial to further improve the coulombic efficiency, cycle performance and safety performance of lithium-ion batteries at the same time.

[0122] As an example, Formula I can be selected from the following chemical formulas: C4H8F2, C4H7F3, C4H6F4, C4H5F5, C4H4F6, C4H3F7, C4H2F8, C4HF9, C5H 10 F2, C5H9F3, C5H8F4, C5H7F5, C5H6F6, C5H5F7, C5H4F8, C5H3F9, C5H2F 10 、C5HF 11 、C6H 12 F2, C6H 11 F3, C6H 10 F4, C6H9F5, C6H8F6, C6H7F7, C6H6F8, C6H5F9, C6H4F 10 、C6H3F 11 、C6H2F 12 、C6H1F 13 、C7H 14 F2, C7H 13 F3, C7H 12 F4, C7H 11 F5, C7H 10 F6, C7H9F7, C7H8F8, C7H7F9, C7H6F 10 、C7H5F 11 、C7H4F 12 、C7H3F 13 、C7H2F 14 、C7HF 15 、C8H 16 F2, C8H 15 F3, C8H 14 F4, C8H 13 F5, C8H 12 F6, C8H 11 F7, C8H 10 F8, C8H9F9, C8H8F 10 、C8H7F 11 、C8H6F 12 、C8H5F 13 、C8H4F 14 、C8H3F 15 、C8H2F 16 or C8HF 17 .

[0123] As an example, Formula II can be selected from the following chemical formulas: C4H6F2, C4H5F3, C4H4F4, C4H3F5, C4H2F6, C4HF7, C5H8F2, C5H7F3, C5H6F4, C5H5F5, C5H4F6, C5H3F7, C5H2F8, C5HF9, C6H 10 F2, C6H9F3, C6H8F4, C6H7F5, C6H6F6, C6H5F7, C6H4F8, C6H3F9, C6H2F 10 、C6HF 11 、C7H 12 F2, C7H 11 F3, C7H 10 F4, C7H9F5, C7H8F6, C7H7F7, C7H6F8, C7H5F9, C7H4F 10 、C7H3F 11 、C7H2F 12 、C7HF 13 、C8H 14 F2, C8H 13 F3, C8H 12 F4, C8H 11 F5, C8H 10 F6, C8H9F7, C8H8F8, C8H7F9, C8H6F 10 、C8H5F 11 、C8H4F 12 、C8H3F 13 、C8H2F 14 or C8HF 15 .

[0124] As an example, Formula III can be selected from the following chemical formulas: C4H4F2, C4H3F3, C4H2F4, C4HF5, C5H6F2, C5H5F3, C5H4F4, C5H3F5, C5H2F6, C5HF7, C6H8F2, C6H7F3, C6H6F4, C6H5F5, C6H4F6, C6H3F7, C6H2F8, C6HF9, C7H 10 F2, C7H9F3, C7H8F4, C7H7F5, C7H6F6, C7H5F7, C7H4F8, C7H3F9, C7H2F 10 、C7HF 11 、C8H 12 F2, C8H 11 F3, C8H 10 F4, C8H9F5, C8H8F6, C8H7F7, C8H6F8, C8H5F9, C8H4F 10、C8H3F 11 、C8H2F 12 or C8HF 13 .

[0125] In some embodiments, the additive is a halogenated hydrocarbon shown in Formula III. The halogenated hydrocarbon shown in Formula III has a degree of unsaturation of 2, which is conducive to forming a more compact and structurally stable inorganic-organic composite SEI film, and is conducive to inhibiting the rupture of the SEI film during lithium deposition and stripping, so as to further improve the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery at the same time.

[0126] In some embodiments, the additive is selected from at least one of the following compounds:

[0127] (C4H8F2, CAS No.: 2358-38-5), (C4H7F3, CAS No.: 66587-70-0), (C4H6F4, CAS No.: 161879-84-1), (C4H5F5, CAS No.: 161879-85-2), (C4H4F6, CAS No.: 407-59-0), (C4H3F7, CAS No.: 86884-16-4), (C4H2F8, CAS No.: 54370-97-7), (C4HF9, CAS No.: 680-17-1), (C5H8F4), (C5H7F5, CAS No.: 154381-43-8), (C5H6F6), (C5H5F7), (C5H2F 10 , CAS No.: 138495-42-8), (C5H6F6, CAS No.: 66711-82-8), (C6H5F9), (C6H5F9, CAS No.: 38436-17-8), (C6H7F7), (C6H5F9), (C6H4F 10 ), (C7H4F 12 ), (C8H6F 12 ), (C6H3F11 ), (C7H4F 12 ), (C6H7F7, CAS No.: 503188-97-4), (C5H7F5, CAS No.: 102526-12-5), (C7H8F8, CAS No.: 503189-07-9), (C8H9F9, CAS No.: 35262-54-5), (C4H6F2, CAS No.: 721946-12-9), (C5H6F4), (C5H5F5, CAS No.: 135671-20-4), (C5H4F6), (C5H3F7), (C6H5F7), (C6H4F8, CAS No.: 159148-08-0), (C6H4F8, CAS No.: 90277-98-8), (C6H3F9, CAS No.: 19430-93-4), (C6H5F7), (C7H6F8), (C8H8F8), (C5H6F4), (C6H4F8), (C6H6F6), (C6H4F8, CAS No.: 830-15-9), (C7H6F8), (C8H8F8), (C4H4F2), (C5H4F4), (C5H3F5), (C5H2F6), (C5HF7), (C6H3F7), (C6H4F6), (C6HF9, CAS No.: 59665-30-4), (C6H3F7), (C7H4F8), (C8H6F8), (C5H4F4, CAS No.: 5239-56-5), (C6H4F6), (C6H4F6), (C7H4F8), (C8H6F8).

[0128] The additive is selected from the above compounds, which can form a dense SEI film during the cycle of the lithium-ion battery, which is beneficial to inhibit the rupture of the SEI film during lithium deposition and stripping, and can improve the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery.

[0129] It should be noted that in other optional embodiments of the present application, the halogenated hydrocarbon is not limited to the compounds listed above, as long as it is a halogenated hydrocarbon.

[0130] In some embodiments, the lithium salt is selected from at least one of lithium trifluoromethanesulfonimide (LITFSI), lithium bis(fluorosulfonyl)imide (LIFSI), and lithium difluorooxalatoborate (LiDFOB). The lithium source is selected from the above substances to form an inorganic fluorine-rich SEI film component, which is beneficial to further improve the cycle performance of the lithium-ion battery.

[0131] As an example, the lithium salt may be only LIFSI, or only LiDFOB, or both LIFSI and LiDFOB.

[0132] It should be noted that in other optional embodiments of the present application, the lithium salt is not limited to the above-mentioned substances. For example, the lithium salt may also include at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate.

[0133] In some embodiments, the solvent is selected from ether solvents.

[0134] In some embodiments, the solvent is selected from at least one of methyl n-butyl ether (MBE), tetrahydrofuran (THF), ethylene glycol dimethyl ether (DME), ethylene glycol diethyl ether (DEE), propylene glycol dimethyl ether, 1,2-dimethoxypropane (DMP1) and 1,3-dimethoxypropane (DMP2).

[0135] Furthermore, in some embodiments, the solvent is selected from at least one of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, 1,2-dimethoxypropane and propylene glycol dimethyl ether. The solvent is selected from the above substances, has good solubility for lithium salts, and can improve the ability to resist oxidation of the positive electrode at high voltage.

[0136] As an example, in the present application, the solvent may be only DME, or the solvent may be only DEE, or the solvent may be only 1,2-dimethoxypropane, or the solvent may be only propylene glycol dimethyl ether, or the solvent may be any two of the above substances, or the solvent may be any three of the above substances, or the solvent may be all of the above substances.

[0137] It should be noted that in other optional embodiments of the present application, the solvent may also be at least one of other carbonate compounds, carboxylate compounds, ether compounds or other organic solvents; wherein the carbonate compounds may include but are not limited to at least one of chain carbonate compounds, cyclic carbonate compounds or fluorinated carbonate compounds; the chain carbonate compounds may include but are not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or methyl ethyl carbonate (MEC); the cyclic carbonates may include but are not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC); the fluorinated carbonate compounds may include but are not limited to fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate , 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate; the above-mentioned carboxylic acid ester compound may include but is not limited to methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid, valerolactone or caprolactone; the above-mentioned ether compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanoic acid, valerolactone or caprolactone; the above-mentioned ether compound may include but is not limited to In at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran; the other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate.

[0138] In some embodiments, the electrolyte further includes a diluent, and the diluent is selected from at least one of fluoroether, benzene (BZ) and anisole.

[0139] The fluoroether refers to a compound containing only carbon atoms, hydrogen atoms, fluorine atoms and oxygen atoms, and the oxygen atoms exist only in the form of ether bonds.

[0140] The diluent is selected from at least one of fluoroether, benzene and anisole, which can improve the problems of high electrolyte viscosity, poor wettability with the diaphragm and low ion conductivity caused by high salt concentration of the electrolyte, and is beneficial to improving the cycle performance, rate performance and safety performance of lithium-ion batteries.

[0141] As an example, in the present application, the diluent may be only fluoroether, or the diluent may be only benzene, or the diluent may be only anisole, or the diluent may be any two of the above substances, or the diluent may be all of the above substances.

[0142] In some embodiments, the molar ratio of the diluent to the lithium salt is ≤ 5. The molar ratio of the diluent to the lithium salt can improve the cycle performance of the lithium ion battery under the above ratio.

[0143] As an example, the ratio of the molar amount of diluent to the molar amount of lithium salt can be any value among 0.01, 0.02, 0.05, 0.07, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.2, 1.5, 1.7, 2, 2.2, 2.5, 2.7, 3, 3.2, 3.5, 3.7, 4, 4.2, 4.5, 4.7 and 5, or a range between any two of them.

[0144] In some embodiments, the additive accounts for 15% to 25% of the total molar amount of the lithium salt, the solvent, and the diluent.

[0145] The value corresponding to the total molar amount of the additive in the lithium salt, the solvent and the diluent refers to the ratio of the molar amount of the additive to the total molar amount of “lithium salt, the solvent and the diluent”.

[0146] When the electrolyte contains a diluent, the additive accounts for 15% to 25% of the total molar amount of the lithium salt, solvent and diluent, and a dense SEI film can be formed during the cycle of the lithium-ion battery, which is beneficial to inhibit the rupture of the SEI film during lithium deposition and stripping, and can simultaneously improve the coulombic efficiency, cycle performance and safety performance of the lithium-ion battery.

[0147] As an example, when the electrolyte contains a diluent, the ratio of the molar amount of the additive to the total molar amount of the lithium salt, the solvent and the diluent can be any value among 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24% and 25%, or a range value between any two of them.

[0148] In some embodiments, the fluoroether is selected from at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl (TFE), 1-(1,1,2,2-tetrafluoroethoxy)propane (TFEPE), 1,1,2,2-tetrafluoroethylethyl ether (ETE), and bis(2,2,2-trifluoroethyl)ether.

[0149] Furthermore, in some embodiments, the diluent is selected from at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl, 1-(1,1,2,2-tetrafluoroethoxy)propane and benzene; which is beneficial to further improve the problems of high electrolyte viscosity, poor wettability with the diaphragm and low ion conductivity caused by the high salt concentration of the electrolyte, and is beneficial to improve the cycle performance, rate performance and safety performance of lithium-ion batteries.

[0150] It should be noted that in other optional embodiments of the present application, the electrolyte may not contain the diluent "fluoroether, benzene and anisole". The above electrolyte can be used to prepare the battery 100, and the prepared battery 100 can inhibit the rupture of the SEI film during lithium deposition and stripping, and can simultaneously improve the coulombic efficiency, cycle performance and safety performance of the lithium ion battery. The battery 100 can be used as a power source for electrical equipment.

[0151] The present application provides a lithium metal battery, which includes the electrolyte provided above. It should be noted that the electrolyte in the lithium metal battery here is the initial state of the electrolyte when the lithium metal battery is assembled, that is, the electrolyte before the lithium metal battery is formed; it is understandable that after the charge and discharge cycle, the composition of the electrolyte will change.

[0152] In the present application, a lithium metal battery refers to a lithium ion battery using metallic lithium or a lithium alloy as the negative electrode active material.

[0153] The lithium metal battery provided in the present application can improve the mechanical strength and stability of SEI, inhibit the rupture of SEI film during lithium deposition and stripping, reduce the side reaction between lithium metal and electrolyte, which is beneficial to avoid short circuit of lithium metal battery, and can simultaneously improve the coulombic efficiency, cycle performance and safety performance of lithium metal battery.

[0154] Next, one or more embodiments are described in more detail with reference to the following examples. Of course, these examples do not limit the scope of one or more embodiments.

[0155] Experimental Example 1

[0156] (1) Prepare electrolyte:

[0157] After the solvent, diluent and additive are evenly mixed, lithium salt is added and stirred thoroughly to obtain an electrolyte. The configuration parameters of the electrolyte are shown in Tables 1 and 2.

[0158] (2) Preparation of positive electrode sheet:

[0159] The positive electrode active material lithium nickel cobalt manganese oxide (NMC811), the conductive agent acetylene black and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 98:1:1 were mixed, and the solvent N-methylpyrrolidone (NMP) was added and stirred until the system became uniform to prepare a positive electrode slurry with a solid content of 50wt%.

[0160] The positive electrode slurry was evenly coated on both sides of the positive electrode current collector aluminum foil (thickness of 10 μm), dried at 20°C, transferred to an oven and continued to dry at 85°C, and then cut into 40 mm × 50 mm rectangles as positive electrode sheets. The surface capacity of the positive electrode sheet was 3.5 mAh / cm 2 .

[0161] (3) Preparation of negative electrode sheet:

[0162] A lithium foil with a thickness of 50 μm was rolled onto a copper foil with a thickness of 8 μm and then cut into a rectangle of 41 mm×51 mm as a negative electrode sheet.

[0163] (4) Preparation of battery cells:

[0164] Take a cut positive electrode sheet and match it with two cut negative electrode sheets, use the above-mentioned separator to isolate the positive electrode sheet and the negative electrode sheet in the middle, and wrap them in an aluminum-plastic film bag to form a laminated dry battery cell. Inject 0.3g of the above-prepared electrolyte, vacuum heat-press the aluminum-plastic film bag, and let it stand at 20°C for at least 6 hours to obtain a battery cell with a rated capacity of 140mAh.

[0165] The isolation membrane is a polyethylene porous membrane, and the thickness of the isolation membrane is 16 μm.

[0166] Table 1 Configuration parameters of electrolyte

[0167]

[0168]

[0169] In Table 1, “ / ” means that there is no corresponding parameter.

[0170] Table 2 Parameters of additives

[0171]

[0172]

[0173]

[0174]

[0175]

[0176] In Table 2, “ / ” means that there is no corresponding parameter.

[0177] The performance of the battery cells prepared in the examples and comparative examples was tested:

[0178] (1) Optical microscopy test of negative electrode:

[0179] At 25°C, the prepared battery cell was first charged to 4.3V at a constant current of 0.2C, and then discharged to 2.8V at a constant current of 0.5C. This was a charge and discharge cycle. After 100 cycles, the battery cell was disassembled, the negative electrode piece was taken out, and a light microscope (instrument model DBX-3020) was used to observe the "SEI film on the surface of the negative electrode piece in contact with the isolation membrane" and the "surface of the isolation membrane in contact with the negative electrode piece", and light microscope photos were taken.

[0180] (2) Cyclic performance test:

[0181] At 25°C, the prepared battery cell is first charged to 4.3V at a constant current of 0.2C, and then discharged to 2.8V at a constant current of 0.5C. This is a charge-discharge cycle process, and the discharge capacity this time is the first-cycle discharge capacity. When the discharge capacity decays to 80% of the first-cycle discharge capacity, the corresponding cycle number of the battery cell is recorded.

[0182] (3) Coulomb efficiency test:

[0183] When testing the coulombic efficiency, the preparation of the battery cell is different from that of the single cell in Experimental Example 1. The difference is that the steps for preparing the negative electrode plate are different, and the negative electrode plate only uses a copper foil with a thickness of 8 μm.

[0184] At 25°C, the battery cell is first charged to 4.3V with a constant current of 0.2C, and the charging capacity is Q1. The battery cell is discharged to 2.8V with a constant current of 0.5C. This is a charge and discharge cycle, and the discharge capacity this time is the first cycle discharge capacity. When the discharge capacity decays to 80% of the first cycle discharge capacity, 0.1C is used to continue to discharge to 2.8V. The discharge capacity of the last cycle (nth cycle) is Qn, and then the coulomb efficiency is calculated as follows = 100×[1-(Q1-Qn)] / Qtotal, where Qtotal is the total charging capacity of the cycle.

[0185] Among them, the performance of the battery monomer is shown in Table 2:

[0186] Table 2 Performance of battery cells

[0187]

[0188]

[0189] Figure 5 The optical microscope images of the surface of the negative electrode plate in contact with the separator and the surface of the separator in contact with the negative electrode plate after the battery cell of Example 2 is cycled 100 times are shown. Figure 5 In the figure, the part labeled A is the surface of the negative electrode sheet in contact with the separator, and the part labeled B is the surface of the separator in contact with the negative electrode sheet; Figure 6 An enlarged optical microscope image of the surface of the negative electrode sheet in contact with the separator after the battery cell of Example 2 has been cycled 100 times is shown; Figure 7 The optical microscope images of the surface of the negative electrode plate in contact with the separator and the surface of the separator in contact with the negative electrode plate after the battery cell of Example 11 is cycled 100 times are shown. Figure 7 In the figure, the part labeled A is the surface of the negative electrode sheet in contact with the separator, and the part labeled B is the surface of the separator in contact with the negative electrode sheet; Figure 8 An enlarged optical microscope image of the surface of the negative electrode sheet in contact with the separator after the battery cell of Example 11 has been cycled 100 times; Fig. 9 The optical microscope images of the surface of the negative electrode plate in contact with the separator and the surface of the separator in contact with the negative electrode plate after 100 cycles of the battery cell of Comparative Example 1 are shown. Fig. 9 In the figure, the part labeled A is the surface of the negative electrode sheet in contact with the separator, and the part labeled B is the surface of the separator in contact with the negative electrode sheet; Fig.10 An enlarged optical microscope image of the surface of the negative electrode sheet in contact with the separator after the battery cell of Comparative Example 1 has been cycled 100 times is shown; Fig.11 The optical microscope images of the surface of the negative electrode sheet in contact with the separator and the surface of the separator in contact with the negative electrode sheet after 100 cycles of the battery cell of Comparative Example 3 are shown. Fig.11 In the figure, the part labeled A is the surface of the negative electrode sheet in contact with the separator, and the part labeled B is the surface of the separator in contact with the negative electrode sheet; Fig.12 An enlarged optical microscope image of the surface of the negative electrode sheet in contact with the separator after the battery cell of Comparative Example 3 has been cycled 100 times is shown.

[0190] The difference between Example 2 and Example 11 and Comparative Example 1 and Comparative Example 3 is that halogenated hydrocarbon additives are used in Example 2 and Example 11, while halogenated hydrocarbon additives are not used in Comparative Example 1 and Comparative Example 3.

[0191] from Figure 5 and Figure 7 and Fig. 9and Fig.11 From the comparison, it can be seen that compared with Comparative Examples 1 and 3, the SEI film formed after 100 cycles of the battery cells of Example 2 and Example 11 is not easy to fall off to the surface of the "isolation film in contact with the negative electrode plate", indicating that the SEI film formed after 100 cycles of the battery cells of Example 2 and Example 11 has stronger adhesion to the lithium foil in the negative electrode plate, is not easy to fall off, and is not easy to enter the electrolyte, is not easy to cause a short circuit, and is safer.

[0192] from Figure 6 and Figure 8 and Fig.10 and Fig.12 It can be seen from the comparison that compared with Comparative Examples 1 and 3, the SEI film formed in Example 2 and Example 11 after 100 cycles of the battery cells is more uniform and dense, the lithium foil in the negative electrode plate is fully covered by the SEI film, and the lithium foil does not leak from the surface of the negative electrode plate; the inventors analyzed that the reason may be: the halogenated hydrocarbons in the electrolyte can make the SEI film an organic-inorganic composite structure, which increases the organic matter content in the SEI film.

[0193] It can be seen from Table 1 and Table 2 that the cycle performance and coulombic efficiency of the battery cells of Examples 1-37 are better than those of Comparative Examples 1-3, indicating that the presence of halogenated hydrocarbons in the electrolyte is beneficial to simultaneously improving the coulombic efficiency and cycle performance of lithium-ion batteries.

[0194] From the comparison of Examples 1-3, it can be seen that the unsaturated bonds in the halogenated hydrocarbons can improve the coulombic efficiency and cycle performance of the lithium-ion battery; and as the unsaturation of the halogenated hydrocarbons increases, the coulombic efficiency and cycle performance of the lithium-ion battery also increase accordingly.

[0195] From the comparison of Examples 4-5, it can be seen that when the atomic composition and atomic ratio of the halogenated hydrocarbon are the same, the presence of fluorine atoms on two adjacent carbon atoms in the halogenated hydrocarbon structure is beneficial to further improve the coulombic efficiency and cycle performance of the lithium-ion battery.

[0196] From the comparison of Examples 6-13, it can be seen that when the number of carbon atoms in the halogenated hydrocarbons is the same, the ratio of the number of fluorine atoms to the number of hydrogen atoms in the halogenated hydrocarbons can further affect the coulombic efficiency and cycle performance of the lithium-ion battery; when the number of carbon atoms in the halogenated hydrocarbons is the same, the ratio of the number of fluorine atoms to the number of hydrogen atoms in the halogenated hydrocarbons is 2-9, which is beneficial to further improve the coulombic efficiency and cycle performance of the lithium-ion battery.

[0197] From the comparison of Examples 14-16, it can be seen that when the atomic composition and atomic ratio of the halogenated hydrocarbon are the same, the halogenated hydrocarbon structural formula contains a cyclic structure or a branched structure, which is beneficial to further improve the coulombic efficiency and cycle performance of the lithium-ion battery.

[0198] From the comparison between Example 9 and Examples 17-20, it can be seen that when the ratio of the number of fluorine atoms to the number of hydrogen atoms in the fluorinated hydrocarbon is the same, the number of carbon atoms in the halogenated hydrocarbon is 5-7, which is beneficial to further improve the coulombic efficiency and cycle performance of the lithium-ion battery.

[0199] From the comparison between Example 2 and Examples 21-24, it can be seen that the molar ratio of fluorinated hydrocarbons to lithium salts in the electrolyte can further affect the coulombic efficiency and cycle performance of the lithium-ion battery; when the molar ratio of lithium salt to additive is 1:(0.05-2), it is beneficial to further improve the coulombic efficiency and cycle performance of the lithium-ion battery.

[0200] From the comparison of Example 2 and Examples 25-28, it can be seen that the molar ratio of the solvent to the lithium salt in the electrolyte can further affect the coulombic efficiency and cycle performance of the lithium ion battery; when the molar ratio of the lithium salt to the solvent is 1:(1.2-2.4), it is beneficial to further improve the coulombic efficiency and cycle performance of the lithium ion battery.

[0201] From the comparison between Example 2 and Examples 29-32, it can be seen that when the electrolyte contains both fluorocarbons and diluents, the percentage of the additive in the total molar amount of the lithium salt, the solvent and the diluent can further affect the coulombic efficiency and cycle performance of the lithium-ion battery.

[0202] From the comparison between Example 2 and Examples 33-34, it can be seen that the fluorinated hydrocarbons contained in the electrolyte of the present application are not only applicable to specific lithium salts. When the lithium salt is selected from LIFSI, LITFSI or LIDFOB, the coulombic efficiency and cycle performance of the lithium-ion battery can be better.

[0203] From the comparison between Example 2 and Example 35, it can be seen that the fluorinated hydrocarbons contained in the electrolyte of the present application are not only applicable to specific solvents, but also can improve the coulombic efficiency and cycle performance of lithium-ion batteries when the solvent is selected from DME or DEE.

[0204] From the comparison between Example 2 and Examples 36-37, it can be seen that the fluorinated hydrocarbon contained in the electrolyte of the present application is not only applicable to specific diluents, but also can improve the coulombic efficiency and cycle performance of lithium-ion batteries when the diluent is selected from TTE, BZ or anisole.

[0205] In summary, the electrolyte of the present application contains halogenated hydrocarbons, which are compounds containing carbon atoms, hydrogen atoms and fluorine halogen atoms, and the halogen atoms include fluorine atoms; halogenated hydrocarbons as additives can improve the mechanical strength and stability of SEI, inhibit the rupture of SEI film during lithium deposition and stripping, reduce the side reaction between lithium metal and electrolyte, help avoid short circuit phenomenon in lithium ion batteries, and improve the coulombic efficiency, cycle performance and safety performance of lithium ion batteries at the same time; in addition, halogenated hydrocarbons can also be used as diluents at the same time, which is helpful to avoid the problems of poor wettability, high viscosity and low ionic conductivity caused by high salt concentration of the electrolyte, and thus help improve the cycle performance, rate performance and safety performance of lithium ion batteries.

[0206] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present application.

Claims

1. An electrolyte, characterized in that: Including lithium salts, solvents and additives; Wherein, the additive is a halogenated hydrocarbon; the halogenated hydrocarbon is a compound containing carbon atoms, hydrogen atoms and halogen atoms; the halogen atoms include fluorine atoms.

2. The electrolyte according to claim 1, characterized in that The halogen atom is a fluorine atom.

3. The electrolyte according to claim 2, characterized in that The molar ratio of the lithium salt, the solvent and the additive is 1:(0.8-3):(0.02-3); Optionally, the molar ratio of the lithium salt, the solvent and the additive is 1:(1.2-2.4):(0.05-2).

4. The electrolyte according to claim 2, characterized in that The number of carbon atoms of the halogenated hydrocarbon is ≤20; And / or, the halogenated hydrocarbon has a branched structure, and both the main chain of the halogenated hydrocarbon and the branched structure have fluorine atoms; And / or, the halogenated hydrocarbon has a cyclic structure; and / or, the ratio of the number of fluorine atoms to the number of hydrogen atoms in the halogenated hydrocarbon is 2-9; and / or, in the halogenated hydrocarbon, at least two adjacent carbon atoms are connected to fluorine atoms; and / or, the halogenated hydrocarbon has an unsaturated bond; Optionally, the halogenated hydrocarbon has 5 to 7 carbon atoms.

5. The electrolyte according to claim 2, characterized in that The additive comprises at least one of the halogenated hydrocarbons shown in formula I, the halogenated hydrocarbons shown in formula II, and the halogenated hydrocarbons shown in formula III; The formula I is: m1 H 2(m1)+2-n1 F n1 , 8≥m1≥4, n1<2×m1+2; The formula II is: m2 H 2(m2)-n2 F n2 , 8≥m2≥4, n2<2×m2; The formula III is: m3 H 2(m3)-2-n3 F n3 , 8≥m3≥4, n3<2×m3-2.

6. The electrolyte according to claim 5, characterized in that The additive is a halogenated hydrocarbon represented by the formula III.

7. The electrolyte according to claim 5, characterized in that The additive is selected from at least one of the following compounds:

8. The electrolyte according to any one of claims 1 to 7, characterized in that The lithium salt is selected from at least one of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide and lithium difluorooxalatoborate; And / or, the solvent is an ether solvent; Optionally, the solvent is selected from at least one of methyl n-butyl ether, tetrahydrofuran, ethylene glycol dimethyl ether, ethylene glycol diethyl ether, propylene glycol dimethyl ether, 1,2-dimethoxypropane and 1,3-dimethoxypropane.

9. The electrolyte according to any one of claims 1 to 7, characterized in that The electrolyte also includes a diluent, and the diluent is selected from at least one of fluoroether, benzene and anisole; Optionally, the ratio of the molar amount of the diluent to the molar amount of the lithium salt is ≤5; Optionally, the additive accounts for 15% to 25% of the total molar amount of the lithium salt, the solvent and the diluent; Optionally, the fluoroether is selected from at least one of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1,1,2,2-tetrafluoroethyl-2,2,2-trifluoroethyl, 1-(1,1,2,2-tetrafluoroethoxy)propane, 1,1,2,2-tetrafluoroethyl ethyl ether and bis(2,2,2-trifluoroethyl) ether.

10. A lithium metal battery, characterized in that: The lithium metal battery comprises the electrolyte according to any one of claims 1 to 9.

11. An electrical device, characterized in that: The electrical device comprises the lithium metal battery according to claim 10.